Extreme Cinema - Knapp, Jonathan; Kerner, Aaron (Edinburgh University Press, 2021)
Extreme Cinema examines the highly stylized treatment of sex and violence in post-millennial transnational cinema, where the governing convention is not the narrative but the spectacle.